WATER POLLUTION IN INDIA: ISSUES AND CHALLENGES - Dr. Jaidev (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Today in India the people are suffering from various water born disease like kidney failure, stomach infection, cholera, jaundice and most of the poor people do not have sufficient money to pay cost of medical treatment. As we have seen in 1983, in India labourer were drinking dirty water from nullah and the government fail to provide them safe drinking water, so these issues are of public importance and needs detailed investigation. In India there are number of sources of drinking water but India is still facing water crisis, in this article I will investigate who is responsible for water pollution, role of government in prevention of water pollution, effectiveness of penalties for water pollution, judicial responses to the environment pollution, and role of NGT regarding water pollution.